ANALISIS PENGELOLAAN MEDIA SOSIAL BIRO ADMINISTRASI PIMPINAN JAWA BARAT - Indria Angga Dianita (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
Social media is a means for mass communication and can serve as a bridge to showcase its users' existence. The Leadership Administration Bureau, or Biro Adpim Jabar, is a government agency in West Java responsible for matters related to leadership administration. However, this Bureau is not widely recognized by the public. The Biro Adpim Jabar manages social media to increase its recognition, especially among the people of West Java. The purpose of this study is to understand how the Biro Adpim Jabar manages its social media. This research employs a descriptive qualitative method through interviews, observations, and literature studies for data collection. The researcher uses Regina Luttrell's The Circular Model of SoMe as a guide to study the social media management of the Biro Adpim Jabar. The results show that the Biro Adpim Jabar implements all stages of The Circular Model of SoMe: Share (understanding goals, sharing content, following trends & consistency), Optimize (optimizing favorite content, features, use of captions & hashtags, and leveraging popular figures and collaborations), Manage (media monitoring, time management, and management of administrators), and Engage (interaction with the audience and organizing contests or campaigns). The study also found some shortcomings in the social media management of the Biro Adpim Jabar, such as the suboptimal use of features on platforms like TikTok, X, and YouTube. The Biro Adpim Jabar tends to focus more on managing Instagram.